THE WEAKNESSES OF ALTERNATIVE INSTITUTIONS FOR DISPUTE RESOLUTION IN FINANCIAL SERVICES SECTOR - Christiani, Theresia Anita; Kastowo, Chryssantus (International Journal of Law Reconstruction, 2021)
There are weaknesses in the Financial Services Authority issued POJK No. 61/POJK/2020 concerning Alternative Dispute Resolution in the financial services sector. It hampered the objectives of the regulation. A concept proposal is needed to overcome the existing weaknesses. This research uses normative juridical analysis.Â  This research dose on the laws and regulations that apply in Indonesia relating to the settlement of disputes in the financial services sector. This study finds a proposed concept to overcome the weaknesses of Alternative Dispute Resolution in the financial services sector. The proposed idea empowers legal culture, legal substance, and legal culture as legal system theory. This research is limited to study based on secondary data, so there is no primary data.